Pengaruh Penilaian Produk dan Harga terhadap Kepuasan Pelanggan serta Dampaknya terhadap Loyalitas Pelanggan PT. Outletz Worldwide Indonesia - Jaenudin, Jaenudin (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to determine the partial and simultaneous influence of product evaluation and price on customer satisfaction, as well as the impact of customer satisfaction on loyalty. The research adopts an associative approach with a quantitative methodology. The population consists of all customers of a minimarket at Koperasi Visiana Bakti TVRI Jakarta, with a sample size of 100 respondents. Data collection was conducted using questionnaires, and data analysis techniques included instrument testing, classical assumption tests, regression analysis, determination coefficient analysis, and hypothesis testing using t-tests and F-tests. The results indicate that product evaluation has a positive and significant effect on customer satisfaction. This suggests that an increase in product evaluation leads to an improvement in customer satisfaction. Additionally, price has a negative and significant effect on customer satisfaction, meaning that a price increase tends to reduce customer satisfaction. When considered simultaneously, both product evaluation and price significantly influence customer satisfaction, contributing substantially to variations in customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty. This implies that an increase in customer satisfaction enhances customer loyalty. The findings highlight the importance of product evaluation and pricing strategies in shaping customer satisfaction, which in turn plays a crucial role in fostering customer loyalty.